Photosensitised heterogeneous oxidation kinetics of biomass burning aerosol surrogates by ozone using an irradiated rectangular channel flow reactor - S. M. Forrester; D. A. Knopf (Atmospheric Chemistry and Physics, 2013)
Heterogeneous reaction kinetics involving organic aerosol and atmospheric oxidants such as ozone can be enhanced under visible or UV irradiation in the presence of a photosensitiser, with subsequent implications for the climate, cloud radiative properties, air quality, and source appointment. In this study we report the steady-state reactive uptake coefficient, γ, of O3 by levoglucosan and 5-nitroguaiacol acting as surrogates for biomass burning aerosol particles, with and without the presence of Pahokee peat acting as a photosensitiser. The reactive uptake has been determined in the dark and as a function of visible and UV-A irradiation and ozone concentration. In addition, γ was determined for 1 : 1, 1 : 10, and 1 : 100 by mass mixtures of Pahokee peat and 5-nitroguaiacol, and for a 10 : 1 : 3 mixture of levoglucosan, Pahokee peat, and 5-nitroguaiacol. We developed a novel irradiated rectangular channel flow reactor (I-RCFR) that was operated under low pressures of about 2–4 hPa, and allowed for uniform irradiation of the organic substrates. The I-RCFR was coupled to a chemical ionisation mass spectrometer and has been successfully validated by measuring the kinetics between various organic species and oxidants. γ of O3 and levoglucosan in the dark and under visible and UV-A irradiation was determined to be in the range of (2–11) × 10−6 and did not change in the presence of Pahokee peat. The determined γ of O3 and 5-nitroguaiacol in the dark was 5.7 × 10−6 and was only enhanced under UV-A irradiation, yielding a value of 3.6 × 10−5. γ of the 1 : 1 Pahokee peat/5-nitroguaiacol substrate was enhanced under visible and UV-A irradiation to 2.4 × 10−5 and 2.8 × 10−5, respectively. Decreasing the amount of Pahokee peat in the 5-nitroguaiacol/Pahokee peat substrate resulted in lower values of γ under visible irradiation, however, γ was consistent under UV-A irradiation regardless of the amount of Pahokee peat. The 10 : 1 : 3 mixture by mass of levoglucosan, Pahokee peat, and 5-nitroguaiacol, under both visible and UV-A irradiation yielded γ values of 2.8 × 10−5 and 1.4 × 10−5, respectively. γ was determined as a function of photon flux for O3 with the 1 : 1 Pahokee peat/5-nitroguaiacol substrate, yielding a linear relationship under both visible and UV-A irradiation. γ of O3 with the 1 : 1 Pahokee peat/5-nitroguaiacol substrate was determined as a function of ozone concentration and exhibited an inverse dependence of γ on ozone concentration, commonly interpreted as a Langmuir–Hinshelwood mechanism. The reactive uptake data have been represented by a Langmuir-type isotherm. From the O3 uptake data under visible irradiation, the following fit parameters have been derived: ks = (5.5 ± 2.7) × 10−19 cm2 s−1 molecule−1 and KO3 = (2.3 ± 2.0) × 10−12 cm3 molecule−1; and under UV-A irradiation: ks = (8.1 ± 2.0) × 10−19 cm2 s−1 molecule−1 and KO3 = (1.7 ± 0.7) × 10−12 cm3 molecule−1. The oxidative power, or the product of γ and [O3], was determined for O3 with the 1 : 1 Pahokee peat/5-nitroguaiacol substrate and was in the range of (1.2–26) × 106 molecule cm−3. Atmospheric particle lifetimes were estimated for a 0.4 μm 5-nitroguaiacol particle as a function of visible and UV-A irradiation and ozone concentration.